2020
DOI: 10.31744/einstein_journal/2020ao5576
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of ultrasound and cross-sectional imaging for detection of small renal masses: anatomic factors and radiologist's experience

Abstract: A comparative study of ultrasound and cross-sectional imaging for detection of small renal masses: anatomic factors and radiologist's experience Estudo comparativo de ultrassonografia e métodos seccionais para detecção de pequenas lesões renais: fatores anatômicos e experiência do radiologista

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Ultrasound (US) is commonly chosen as the initial modality to assess a renal mass due to ease of accessibility, speed, cost, and the absence of radiation. Despite the clinical advantages of US, it has been shown that US is less sensitive than contrast‐enhanced CT/MRI for the assessment of renal lesions, 15 in particular small lesions such as NRs. On US, PLNRs and ILNRs may be seen as well‐circumscribed hypoechoic nodules and indistinct hypoechoic nodules, respectively 2,16 .…”
Section: Current Aspects Of Radiology and Limitationsmentioning
confidence: 99%
“…Ultrasound (US) is commonly chosen as the initial modality to assess a renal mass due to ease of accessibility, speed, cost, and the absence of radiation. Despite the clinical advantages of US, it has been shown that US is less sensitive than contrast‐enhanced CT/MRI for the assessment of renal lesions, 15 in particular small lesions such as NRs. On US, PLNRs and ILNRs may be seen as well‐circumscribed hypoechoic nodules and indistinct hypoechoic nodules, respectively 2,16 .…”
Section: Current Aspects Of Radiology and Limitationsmentioning
confidence: 99%